1959
DOI: 10.1007/bf01937854
|View full text |Cite
|
Sign up to set email alerts
|

Änderungen der Peroxydase- und Katalasereaktion des Blattes während der Entwicklung

Abstract: In einer friiheren Arbeit (Sc~IWA]~ZE 1954) wurde berichtet, da2 Entwicklungsst5rungen der verschiedensten Art zu einem Anstieg der Peroxydasereaktion in den Blattern ftihren und da2 damit in der Regel ein Absinken des Eiweil3gehaltes und des Verh~Itnisses EiweiB-N/15sl. I~ verbunden ist. Diese Untersuchungen wurden an gestSrten Phaseolusund Epilobium-Bastarden, an Magnesium-, Stiekstoff-und Eisenmangelpflanzen und an isolierten Phaseolus-B]~ttern durchgefiihrt. In der vorliegenden Arbeit wird geprtift, ob der… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

1961
1961
1972
1972

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…However, the values obtained for the photosynthetically mature leaves agree with estimates obtained by other methods. Cellular fractionation in non-aqueous medium (2, 11) of autotrophically-grown Euglena has shown that 65 to 75 % of the transketolase activity is localized in the chloroplast (27 (14), polyphenoloxidase (tea) (18), peroxidase and catalase (sunflower & tobacco) (22), amine oxidase (pea) (35), succinoxidase (tobacco) (17), oxidative phosphorylation (pea) (31), and pentose phosphate cycle enzymes (tobacco) (5). In some instances, there was a slight increase in activity at the time of early leaf expansion.…”
Section: Discussionmentioning
confidence: 99%
“…However, the values obtained for the photosynthetically mature leaves agree with estimates obtained by other methods. Cellular fractionation in non-aqueous medium (2, 11) of autotrophically-grown Euglena has shown that 65 to 75 % of the transketolase activity is localized in the chloroplast (27 (14), polyphenoloxidase (tea) (18), peroxidase and catalase (sunflower & tobacco) (22), amine oxidase (pea) (35), succinoxidase (tobacco) (17), oxidative phosphorylation (pea) (31), and pentose phosphate cycle enzymes (tobacco) (5). In some instances, there was a slight increase in activity at the time of early leaf expansion.…”
Section: Discussionmentioning
confidence: 99%
“…Bei den beiden ersten Arbeitsbypothesen muf^ aber beruckslchtlgt werden, daR die Ursadie fiir die Abwanderung der Tiere audi prlmiir die mani;i-lliafte Verwertbarkeit der Nahrung sein kann. Gegen eine derartige Erkliirung sprechen jedoch die Untersuchungen von SCHALLER (1959) (SHIROYA, SniROYA und HATTORI 1935, CAL.IACHJAN und BOJARKIN 1955, AHLGRIMM 1956, SPRI-CHFR 1956, FORTINI 1956, HENKI: 1958, SCHWARZE 1959 u. a.).…”
Section: Einieitungunclassified